The use of novel measures to detect Accelerated Long-term forgetting in people with epilepsy: The Crimes Test and Four Doors Test. (August 2021) - Laverick, Tom; Evans, Stephen; Freeston, Mark; Baddeley, Alan
Abstract: Most patients with memory disorders appear to forget at a relatively normal rate. Hence testing retention beyond the initial test session becomes unnecessary. However, it is now well established that a subsample of patients, most notably people with epilepsy, can show substantially increased forgetting rates even when acquisition rate is normal, raising the need for new tests focused on the assessment of long-term forgetting. Our study is part of the process of developing two such tests. Both focus on the need to test the same person several times and address the problem that each successive test may interfere with the memory of the event being tested. Depending on conditions, such effects can be substantial and may be either positive or negative. The Crimes and Four Doors Tests tackle this problem by presenting easily memorised episodes or scenes, from which a different sample of features is tested at each delay by telephone. We apply these two novel tests to assess rates of forgetting in groups of people with epilepsy and a matched control group. Both the visual and verbal tests showed clear evidence of accelerated forgetting in the epilepsy group supporting the potential value of the tests as convenient and sensitive measures of the rate of long-term forgetting.